Hubungan Tingkat Kecemasan dengan Kualitas Tidur dalam Menyusun Skripsi pada Mahasiswa Tingkat Akhir Prodi Sarjana Keperawatan Universitas Muhammadiyah Sukabumi - Winda Lestari; Ernawati Hamidah; Hadi Abdillah (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2024)
Background: The biggest demand from students is that during the final semester, students are required to complete their final assignments. Inhibitory problems when preparing a final assignment can cause psychological disorders, which can cause anxiety. Continuous anxiety can affect sleep quality. The less anxious you are in preparing your thesis, the better the student's sleep quality and the more anxious you are, the worse the student's sleep quality. Research Objective: to determine the relationship between anxiety levels and sleep quality in preparing final year undergraduate students' thesis in the undergraduate nursing study program at Muhammadiyah University, Sukabumi. Method: The research used was descriptive correlational with a cross sectional approach with a total sampling method. Respondents in this study were 55 people. Measurements were carried out using the Zung-Self Anxiety Rate Scale (Z-SARS) questionnaire and the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Results: Based on the results of the Chi Square statistical test, it shows a p-value of 0.010 (p-value < 0.05). Conclusion: There is a relationship between anxiety levels and sleep quality in preparing a thesis for final year students of the Bachelor of Nursing Study Program, Muhammadiyah University, Sukabumi.